2010
DOI: 10.21608/eajbsa.2010.15190
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dipterous flies with veterinary importance in selected sheep's farms and slaughter houses in Jazan, Saudi Arabia

Abstract: vegans (Haliday) was the most abundant species followed by Anatricus erianceus Loew and they represented 72.74% and 21.71% of the total collection, respectively. On the other hand, Culicoides imicola Kieffer, Sarcophaga ruficornis (Fabricius) and Musca lucidula (Loew) were recorded in few numbers and they represented 0.09%-0.1% of the total collection. Physiphora alceae (Preyssler) and Musca sorbens Wiedemann were recorded only from slaughter houses. In addtion, Sarcophaga dux Thompson is recorded for the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
(9 reference statements)
1
11
0
Order By: Relevance
“…The only available report from Asir is the report of the tumbu fly, Cordylobia anthropophaga Blanchard (F. Calliphoridae) (Omar & Abdalla, 1992). In the adjacent Province Jazan, Musca domestica, M. domestica calleva, M. sorbens, M. lucidula, Chrysomya albiceps, C. marginalis, Sarcophaga ruficornis, S. dux, Wohlfahrtia indigens, Physiphora alceae, Anatrichus erinaceus, Coproica vagans and Oestrus ovis from farms and slaughter houses were collected (Bosly, 2010(Bosly, , 2013. In other parts of the Kingdom (Ryiadh, Al-Ahsa, Hail and Buraydah Provinces), the following species were reported: Megaselia scalaris, Chrysomya bezziana, C. albiceps, C. rufifacies, Wohlfahrtia nuba, the cluster fly Pollenia rudis (F. Calliphoridae), Oestrus ovis, Cephalopina titillator (F. Oestridae).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only available report from Asir is the report of the tumbu fly, Cordylobia anthropophaga Blanchard (F. Calliphoridae) (Omar & Abdalla, 1992). In the adjacent Province Jazan, Musca domestica, M. domestica calleva, M. sorbens, M. lucidula, Chrysomya albiceps, C. marginalis, Sarcophaga ruficornis, S. dux, Wohlfahrtia indigens, Physiphora alceae, Anatrichus erinaceus, Coproica vagans and Oestrus ovis from farms and slaughter houses were collected (Bosly, 2010(Bosly, , 2013. In other parts of the Kingdom (Ryiadh, Al-Ahsa, Hail and Buraydah Provinces), the following species were reported: Megaselia scalaris, Chrysomya bezziana, C. albiceps, C. rufifacies, Wohlfahrtia nuba, the cluster fly Pollenia rudis (F. Calliphoridae), Oestrus ovis, Cephalopina titillator (F. Oestridae).…”
Section: Discussionmentioning
confidence: 99%
“…The link between human pathogens and fly transmission is due to the fact that the adults feed on animal manure, trash, human excrement and other decaying materials; readily moving between these substrates and food, food preparation surfaces and human themselves (Chaiwong et al, 2012). Although several reports on flies in some parts of Saudi Arabia which were mainly concerned with animal myiasis (Amoudi et al, 1989;Amoudi, 1993;Eesa & el-Sibae, 1993;Fatani & Hilali, 1994;Alahmed, 2000;Al-Misned, 2003;Alahmed, 2004;El-Azazy & El-Metenawy, 2004;Gad Allah & Bosly, 2006) and few sporadic surveys in south-western Saudi Arabia (Buttiker et al, 1979;Omar & Abdalla, 1992;Bosly, 2010) no report on fly surveys in Astir Province is available. Accordingly, the present study aimed to examine the dipterous flies associated with slaughterhouses in Asir Province in the southwest of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Setyaningrum and Al Dhafer (2014) reported these flies from eight provinces, and Mashaly et al (2017) reported finding them in Arar (Northern province). Furthermore, C. albiceps have been recorded on different animal carcasses, such as on sheep (Alahmed 2004;Bosly 2010;Mashaly et al 2017), rabbit (Mashaly et al 2020;Shaalan et al 2017), camel, dog and goat carcasses (Mashaly et al 2019). In addition, C. albiceps have been recorded on human corpses in Saudi Arabia by Al-Shareef andZaki (2017), Al-Qahtni et al (2019) and Al-khalifa et al (2020), in line with evidence from many other countries (Grassberger et al (2003) in Austria, Kosmann et al (2011) in Brazil, Klekovska et al (2017) in the Republic of Macedonia, Bugelli et al (2018) in Italy, Bernhardt et al (2018) in Germany, Moemenbellah-Fard et al (2018) in Iran and Corrêa et al (2019) in India).…”
Section: Genusmentioning
confidence: 99%
“…(2017) reported finding them in Arar (Northern province). Furthermore, C. albiceps have been recorded on different animal carcasses, such as on sheep (Alahmed 2004; Bosly 2010; Mashaly et al . 2017), rabbit (Mashaly et al .…”
Section: Introductionmentioning
confidence: 99%
“…Fauna in Jazan region showed little interest, no detailed studies about the diversity of insects, except very few works, carried out on certain insect groups. Studies such as on mosquito larval survey ( Abdullah and Merdan, 1995 ), phlebotomus species in Asir region ( Ibrahim and Abdoon, 2005 ), Dipterous flies ( Bosly, 2010 ), Mosquitos ( AlAhmed et al, 2010 ) and recently on Chloropidae (Diptera) ( Dawah et al, 2020 ). Hence, because of the scarcity of knowledge regarding the insect fauna of Jazan Dam region, the present work interested in collecting information about the hymenopterous insect fauna survey in Jazan Lake dam region.…”
Section: Introductionmentioning
confidence: 99%